Hubungan Antara Regulasi Emosi dengan Kesejahteraan Psikologis pada Mahasiswa Universitas Aisyah Pringsewu - Rismawati Rismawati; Rima Wilantika (Journal on Education, 2023)
Psychological well-being in students is a form of happiness or satisfaction for a student, where he can feel his psychological condition is good, prosperous, comfortable and positive so that he can function optimally and effectively in living his life as a student. This research aims to determine the relationship between emotional regulation and psychological well-being in Aisyah Pringsewu University students. The design used in this research is correlation using a survey approach. The population in this study were all students at Aisyah Pringsewu University. There were 106 research subjects from various study programs at Aisyah Pringsewu University. Data analysis used Product Moment correlation to test the correlation and showed the results that there was a positive relationship between emotional regulation and psychological well-being in students (r = 0.530; p = 0.000). This shows that the higher a student's emotional regulation, the higher his psychological well-being, conversely, when a student has low emotional regulation, he also has low psychological well-being.